Surfactant protein A alters endosomal trafficking of influenza A virus in macrophages - Yau, Eric; Yang, Linlin; Chen, Yan; Umstead, Todd M.; Atkins, Hannah; Katz, Zoe E.; Yewdell, Jonathan W.; Gandhi, Chintan K.; Halstead, E. Scott; Chroneos, Zissis C. (Frontiers in Immunology, 2023)
Influenza A virus infection (IAV) often leads to acute lung injury that impairs breathing and can lead to death, with disproportionate mortality in children and the elderly. Surfactant Protein A (SP-A) is a calcium-dependent opsonin that binds a variety of pathogens to help control pulmonary infections by alveolar macrophages. Alveolar macrophages play critical roles in host resistance and susceptibility to IAV infection. The effect of SP-A on IAV infection and antiviral response of macrophages, however, is not understood. Here, we report that SP-A attenuates IAV infection in a dose-dependent manner at the level of endosomal trafficking, resulting in infection delay in a model macrophage cell line. The ability of SP-A to suppress infection was independent of its glycosylation status. Binding of SP-A to hemagglutinin did not rely on the glycosylation status or sugar binding properties of either protein. Incubation of either macrophages or IAV with SP-A slowed endocytic uptake rate of IAV. SP-A interfered with binding to cell membrane and endosomal exit of the viral genome as indicated by experiments using isolated cell membranes, an antibody recognizing a pH-sensitive conformational epitope on hemagglutinin, and microscopy. Lack of SP-A in mice enhanced IFN expression, viral clearance and reduced mortality from IAV infection. These findings support the idea that IAV is an opportunistic pathogen that co-opts SP-A to evade host defense by alveolar macrophages. Our study highlights novel aspects of host-pathogen interactions that may lead to better understanding of the local mechanisms that shape activation of antiviral and inflammatory responses to viral infection in the lung.